ChemInform Abstract: Regioselective One‐Pot Synthesis of New Unsymmetric Spiro Dihydrofurans in the Reaction of Mixed Two Different Cyclic β‐Dicarbonyl Compounds with BrCN and Aldehydes in the Presence of Et3N. Issue 32 (August 2015) - Noroozi Pesyan, Nader; Shokr, Alireza; Gharib, Ali; Tunc, Tuncay; Sahin, Ertan
Abstract One‐pot reaction of cyclic β‐dicarbonyl with various aldehydes in the presence of cyanogen bromide and triethylamine leads to the selective and efficient formation of crossed new unsymmetrical spiro dihydrofurans at room temperature (no yields given).